2014
DOI: 10.2337/dc14-1803
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Glucose Homeostasis, Lipids and Lipoproteins, HDL Functionality, and Cardiometabolic Parameters in Modestly Severely Obese African Americans and White Americans With Prediabetes: Implications for the Metabolic Paradoxes

Abstract: OBJECTIVETo determine whether modestly severe obesity modifies glucose homeostasis, levels of cardiometabolic markers, and HDL function in African Americans (AAs) and white Americans (WAs) with prediabetes.RESEARCH DESIGN AND METHODSWe studied 145 subjects with prediabetes (N = 61 WAs, N = 84 AAs, mean age 46.5 ± 11.2 years, mean BMI 37.8 ± 6.3 kg/m2). We measured fasting levels of lipids, lipoproteins, and an inflammatory marker (C-reactive protein [CRP]); HDL functionality (i.e., levels of paraoxonase 1 [PON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
0
17
1
Order By: Relevance
“…Low serum PON activity levels have been associated with an increased risk for major adverse cardiovascular events (MACE), including myocardial infarction and stroke in an American study [ 29 ]. The novel finding of higher PON activity levels in black women compared to white women, independent of protein expression levels is in contrast to other studies in the USA that found that African Americans had lower or similar PON activity levels than their white counterparts, despite similar HDL-C concentrations [ 30 , 31 ].…”
Section: Discussioncontrasting
confidence: 75%
“…Low serum PON activity levels have been associated with an increased risk for major adverse cardiovascular events (MACE), including myocardial infarction and stroke in an American study [ 29 ]. The novel finding of higher PON activity levels in black women compared to white women, independent of protein expression levels is in contrast to other studies in the USA that found that African Americans had lower or similar PON activity levels than their white counterparts, despite similar HDL-C concentrations [ 30 , 31 ].…”
Section: Discussioncontrasting
confidence: 75%
“…reported that GE deteriorates as body mass index (BMI) increases in nondiabetic individuals, whereas Healy et al . reported contrasting findings [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…2). Similarly, in the study by Healy et al (20), modestly severe obesity attenuated the ethnic differences in insulin sensitivity. Of note, when African American and Caucasian patients were matched for adiposity, insulin sensitivity was also similar between ethnic groups (19).…”
Section: Discussionmentioning
confidence: 73%
“…Genetic variations of apoCI, apoCIII, and apoE have also been reported in African American subjects with different frequencies than in Caucasian subjects (27,28). Also, previous studies have found that paraoxonase-1 (PON1) is lower in African Americans compared with Caucasians, suggesting potential HDL-C dysfunction in this ethnic group (20).…”
Section: Discussionmentioning
confidence: 95%